1997
DOI: 10.1111/j.1528-1157.1997.tb01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hippocampal Atrophy: A Serial Magnetic Resonance Imaging Study in a Patient Who Developed Epilepsy After Generalized Status Epilepticus

Abstract: Summary:Purpose: To investigate changes in hippocampal volume.Methods: We used serial magnetic resonance imaging (MRI) in a patient who developed chronic epilepsy after having generalized tonic-clonic status epilepticus (SE). Five MRI investigations were performed during SE and a 58-month follow-up period. Hippocampal volumetric measurements and coregistration of scans were performed to detect hippocampal atrophy.Results: During status both mesiotemporal regions returned a high signal on T,-weighted images. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 7 publications
5
56
0
3
Order By: Relevance
“…These cases are interpreted as evidence of hippocampal injury rather than the natural history of a disease such as focal encephalitis. Wieshmann et al [17] reported bilateral increased T 2 signal in an adult after prolonged generalized seizures. Hippocampal atrophy was present bilaterally at 2 months and progressive bilateral atrophy subsequently occurred.…”
Section: Discussionmentioning
confidence: 99%
“…These cases are interpreted as evidence of hippocampal injury rather than the natural history of a disease such as focal encephalitis. Wieshmann et al [17] reported bilateral increased T 2 signal in an adult after prolonged generalized seizures. Hippocampal atrophy was present bilaterally at 2 months and progressive bilateral atrophy subsequently occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, there is also considerable evidence that several forms of status epilepticus including convulsive tonicclonic status are associated with significant brain damage. Such lesions may be detected using neuropathological methods [7] but also through tailored imaging studies such as quantitative MRI [17,19,26]. However, the answer to the question whether milder forms of status or repetitive isolated seizures that are associated with different pathophysiological processes do also cause structural brain damage remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of 18 F-FDG PET in extratemporal lobe epilepsy (ETLE) is generally reported to be less than that in TLE, but 30%-50% of patients with ETLE are successfully localized-including some patients with a normal MRI in whom the PET findings are critical to allowing that patient to proceed to surgery (8,9,20,21). However, despite this information, the evidence for the cost-effectiveness of 18 F-FDG PET in the presurgical evaluation continues to be questioned by several authors and funding organizations (8,(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%